Motyw winy Heleny w tradycji epickiej i w dyskursie - Zieliński, Karol (Collectanea Philologica, 2021)
The paper takes up the issue of Helen’s guilt for the outbreak of the Trojan war present in the Iliad and in the oral epic tradition. It puts forward a thesis that in order to blame others or to free themselves from blame epic heroes employ the typical in oral culture technique of conducting disputes. Like other characters in the Iliad, Helen, is also under constant social pressure which seeks to find her guilty and, in effect, to activate a mechanism of making a scapegoat of her. To defend herself, she risks self-accusations in order to make it impossible for other people to bring a charge against her. Helen cares about her good opinion in the Trojan society and particularly in the circle of women.